2021
DOI: 10.1101/2021.07.26.453765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Affinity maturation for an optimal balance between long-term immune coverage and short-term resource constraints

Abstract: In order to target threatening pathogens, the adaptive immune system performs a continuous reorganization of its lymphocyte repertoire. Following an immune challenge, the B cell repertoire can evolve cells of increased specificity for the encountered strain. This process of affinity maturation generates a memory pool whose diversity and size remain difficult to predict. We assume that the immune system follows a strategy that maximizes the long-term immune coverage and minimizes the short-term metabolic costs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…Quantitative frameworks to model immune diversity and clone abundance have revealed that simple low-level interactions can give rise to complex outcomes including broad distributions of clone abundance [1, 2, 3, 4, 5, 6], long-lived biologically realistic transient states [7, 5], and clonal restructuring following immune challenges [8, 9, 10, 11, 5]. Phenomenological models of pathogen co-evolution with the immune system have accelerated our understanding of how the fitness landscape generated by the immune system constrains pathogen evolution [12, 13, 7, 14, 15], how the adaptive immune system responds to rapid pathogen evolution [16, 17, 14, 15], and what drives pathogen extinction [7, 13] or the extinction of particular clonal cell lineages [17, 10]. These models have also explored trade-offs such as between immune receptor specificity and cross-reactivity [4, 18], between the specifity of host-pathogen discrimination and sensitivity to pathogens [8, 19, 20], between the speed of an immune response and the efficiency of that response [14], or between metabolic resource use and immune coverage [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative frameworks to model immune diversity and clone abundance have revealed that simple low-level interactions can give rise to complex outcomes including broad distributions of clone abundance [1, 2, 3, 4, 5, 6], long-lived biologically realistic transient states [7, 5], and clonal restructuring following immune challenges [8, 9, 10, 11, 5]. Phenomenological models of pathogen co-evolution with the immune system have accelerated our understanding of how the fitness landscape generated by the immune system constrains pathogen evolution [12, 13, 7, 14, 15], how the adaptive immune system responds to rapid pathogen evolution [16, 17, 14, 15], and what drives pathogen extinction [7, 13] or the extinction of particular clonal cell lineages [17, 10]. These models have also explored trade-offs such as between immune receptor specificity and cross-reactivity [4, 18], between the specifity of host-pathogen discrimination and sensitivity to pathogens [8, 19, 20], between the speed of an immune response and the efficiency of that response [14], or between metabolic resource use and immune coverage [15].…”
Section: Introductionmentioning
confidence: 99%
“…Phenomenological models of pathogen co-evolution with the immune system have accelerated our understanding of how the fitness landscape generated by the immune system constrains pathogen evolution [12, 13, 7, 14, 15], how the adaptive immune system responds to rapid pathogen evolution [16, 17, 14, 15], and what drives pathogen extinction [7, 13] or the extinction of particular clonal cell lineages [17, 10]. These models have also explored trade-offs such as between immune receptor specificity and cross-reactivity [4, 18], between the specifity of host-pathogen discrimination and sensitivity to pathogens [8, 19, 20], between the speed of an immune response and the efficiency of that response [14], or between metabolic resource use and immune coverage [15]. All of these models have shown rich dynamics and qualitatively different states of diversity and evolution arising from simple rules.…”
Section: Introductionmentioning
confidence: 99%
“…Here the connection to our deliberation parameter (β) is even clearer as we chose our naïve cost to be a monotonic function of β. With this clear mapping to our model, it is no surprise that [101] finds the same three regimes described above, while their model relies on more assumptions of the actual biological process.…”
Section: Optimal Memory Of the Immune Systemmentioning
confidence: 52%
“…Thus, even though some states are suboptimal, the population will not die out because it does not have a fitting solution. This tradeoff between the possible gain in one environment and preparation for other environments illustrates a vital component of these models, namely, focusing on long-term growth, not short-term gains, similar to many other studies [96][97][98][99][100][101]. This concept is also the basis for the optimizations in this thesis.…”
Section: Models Of Co-evolutionmentioning
confidence: 68%
See 1 more Smart Citation